Beautiful Pietàs in South Tyrol (Northern Italy): local or imported works of art? - Dariz, Petra; Wortmann, Ulrich G.; Vogl, Jochen; Schmid, Thomas (Heritage science, 2022)
The study, dedicated to Beautiful Pietàs conserved in South Tyrol (Northern Italy), aims to establish, for the first time, a connection between Austroalpine raw materials and the high-fired gypsum mortars constituting the Gothic figure groups in question. The origin and chronology of this stylistically and qualitatively differing ensemble have been subject of art historical debate for nearly a century. The discourse is dominated by three main hypotheses: itinerary of an Austrian artist versus itinerary of the work of art created in an artist’s workshop in Austria versus itinerary of the stylistic vocabulary via graphical or three-dimensional models. The comparison of the δ 34 S values and the 87 Sr/ 86 Sr ratios of the gypsum mortars and Austroalpine sulphate deposits (in a compilation of own reference samples and literature data) points to the exploitation of sediments in the Salzkammergut and possibly also in the evaporite district of the Eastern Calcareous Alps, thus evidencing the import of the sculptures and not the activities of local South Tyrolean or itinerant artists. Two geochronological units are distinguishable: The Pietà in the Church St. Martin in Göflan can be assigned to Upper Permian raw material, whereas the metrologically consistent sculptures in the Church of Our Lady of the Benedictine Abbey Marienberg and in the Chapel St. Ann in Mölten correlate with deposits of the Early Triassic (or the Lower-Middle Triassic transition). The medieval gypsum mortars also differ in their mineralogical characteristics, i.e. in their geologically related minor components, as in the first case, characterised by a significant proportion of primary anhydrite, natural carbonate impurities mainly consist of calcite (partly converted to lime-lump-like aggregates), whereas in the second group dolomite (or rather its hydration products after pyrometamorphic decomposition) predominates, accompanied by celestine, quartz and potassium feldspar. The Pietà in the Cathedral Maria Himmelfahrt in Bozen turned out to be made of Breitenbrunn calcareous sandstone (Leitha Mountains, Burgenland, Austria), which is why the sample is not considered in the geochemical analysis. Graphical Abstract